Department of Anaesthesiology and Critical Care, Lady Hardinge Medical College and Associated Shrimati Sucheta Kriplani Hospital, Connaught Place, New Delhi, India - Singh, Ranju; Saini, Surbhi; Biswas, Ratna (International Journal of Research in Medical Sciences, 2022)
Background: Currently phenylephrine (PE) is recommended to treat hypotension after spinal anesthesia for cesarean delivery (CD). Recently low dose norepinephrine has been proposed as effective alternative with advantage of less depression of maternal heart rate and cardiac output. Methods: This was prospective observational study in women scheduled for CD under spinal anesthesia, patients received either PE 100 µg (group PE) or norepinephrine 8 µg (group NE). Primary objective was to study the difference in umbilical artery pH with use of both drugs. The secondary objectives were to compare maternal hemodynamics, number of boluses required and neonatal outcome. Results: Total 593 patients were enrolled and 226 patients who developed post-spinal hypotension were analysed, 106 patients received PE and 120 patients received norepinephrine. Umbilical artery pH was similar in both groups (p=0.199) but in fetal distress, pH was acidotic in both groups with a greater dip with PE than norepinephrine (p<0.001). Incidence of bradycardia was significantly higher with PE (p<0.001) and number of boluses was greater with norepinephrine. No difference observed in episodes of hypotension and neonatal outcome. Conclusions: Fetal pH was maintained within normal range with both drugs but in fetal distress, fetal pH was acidotic in both groups, however better maintained with norepinephrine than PE. Norepinephrine was as effective as PE for post-spinal hypotension, with lower incidence of bradycardia and similar neonatal outcome. Norepinephrine is recommended to prevent hypotension in CD, particularly in fetal distress. However, further research is needed to confirm this.